Immersive brain puzzle: a virtual reality application aimed at the rehabilitation of post-stroke patients - Araujo, Juliana de Fatima Ovidio; Ribeiro, Elvis Hernandes; Guimaraes, Marcelo de Paiva; Brega, Jose Remo Ferreira [UNESP]; Brandao, Alexandre Fonseca; Dias, Diego Roberto Colombo; Rocha, A.; Goncalves, R.; Penalvo, F. G.; Martins, J. (Ieee, 2021)
Stroke is the disease that most causes disability in the world due to the many recurrences that can affect the individuals. In this context, this study addresses the proposal and implementation of the Immersive Brain Puzzle that aims to assist the rehabilitation of post-stroke patients and stimulate motor and cognitive activities (dual task) by presenting a virtual reality puzzle. It is assumed that treatment in the first hours after a stroke event can significantly contribute to the patient's progress and recovery; thus, our application was developed to be used in the intensive care unit (ICU). The next stage of this research consists of its validation within the hospital environment to be carried out at the Brazilian Institute of Neuroscience and Neurotechnology (CEPID BRAINN) - Unicamp.
Keywords: Virtual reality; Rehabilitation; Stroke